Effect of Sex and Lateral Ankle Sprain History on Dorsiflexion Range Of Motion Asymmetry During the Weight Bearing Lunge Test - kathrine P Cady; Mark De Ste Croix; Martine Deighan (International Journal of Sports Physical Therapy)
# Background